2017
DOI: 10.1089/ars.2016.6888
|View full text |Cite
|
Sign up to set email alerts
|

The SAMHD1 dNTP Triphosphohydrolase Is Controlled by a Redox Switch

Abstract: Here we report that SAMHD1 is a major target for redox regulation of nucleotide metabolism and cell cycle control. SAMHD1 is a triphosphate hydrolase, whose function involves regulation of deoxynucleotide triphosphate pools. We demonstrate that the redox state of SAMHD1 regulates its catalytic activity. We have identified three cysteine residues that constitute an intrachain disulfide bond "redox switch" that reversibly inhibits protein tetramerization and catalysis. We show that proliferative signals lead to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 59 publications
(68 reference statements)
1
63
0
Order By: Relevance
“…The sequential activation and assembly of the SAMHD1 tetramer occur at dNTP concentrations multiple orders of magnitude below the K M . Thus, while reported K M values for SAMHD1 vary considerably from 50–350 μM depending on the study, standard Michaelis-Menten kinetic models apply under all the experimental conditions measured (55, 57, 73, 78, 81, 82). Given the steady-state conditions of an activated SAMHD1 tetramer, the turnover rate for each substrate appears to depend solely on its particular affinity for the active site and its intracellular concentration.…”
Section: Samhd1 Activation Catalysis and Regulationmentioning
confidence: 96%
See 3 more Smart Citations
“…The sequential activation and assembly of the SAMHD1 tetramer occur at dNTP concentrations multiple orders of magnitude below the K M . Thus, while reported K M values for SAMHD1 vary considerably from 50–350 μM depending on the study, standard Michaelis-Menten kinetic models apply under all the experimental conditions measured (55, 57, 73, 78, 81, 82). Given the steady-state conditions of an activated SAMHD1 tetramer, the turnover rate for each substrate appears to depend solely on its particular affinity for the active site and its intracellular concentration.…”
Section: Samhd1 Activation Catalysis and Regulationmentioning
confidence: 96%
“…A recent study demonstrated that SAMHD1 catalytic activity is regulated by redox signaling (82). Redox signaling takes the form of reactive oxygen species (ROS) that are generated by cellular oxidases in response to growth factors binding and activating cellular receptors (130).…”
Section: Samhd1 Cellular Regulation and Nucleotide Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2015, our laboratory developed a sensitive and efficient method for mapping protein disulfide bonds from simple or complex samples (Lu et al . in Nat Methods 12:329, 2015). This method is based on liquid chromatography–mass spectrometry (LC–MS) and a powerful data analysis software tool named pLink.…”
mentioning
confidence: 99%